Association of the ACTN3 R557X polymorphism with glucose tolerance and gene expression of sarcomeric proteins in human skeletal muscle - Riedl, Isabelle (Physiol Rep, 2015)
A common polymorphism (R577X) in the α-actinin (ACTN) 3 gene, which leads to complete deficiency of a functional protein in skeletal muscle, could directly influence metabolism in the context of health and disease. Therefore, we tested the hypothesis that states of glucose tolerance are associated with the ACTN3 R577X genotype. We analyzed the prevalence of the ACTN3 R577X polymorphism in people with normal glucose tolerance (NGT) and type 2 diabetes (T2D) and measured muscle-specific α-actinin 2 and 3 mRNA and protein abundance in skeletal muscle biopsies. Furthermore, we investigated the protein abundance of the myosin heavy chain isoforms and the components of the mitochondrial electron transport chain in skeletal muscle from people with NGT or T2D. mRNA of selected sarcomeric z-disk proteins was also assessed. Although the prevalence of the ACTN3 577XX genotype was higher in T2D patients, genotype distribution was unrelated to metabolic control or obesity. ACTN2 and ACTN3 mRNA expression and protein abundance was unchanged between NGT and T2D participants. Protein abundance of mitochondrial complexes II and IV was related to genotype and glucose tolerance status. Gene expression of sarcomeric z-disk proteins was increased in skeletal muscle from NGT participants with the ACTN3 577XX genotype. While genetic variation in ACTN3 does not influence metabolic control, genotype does appear to influence gene expression of other sarcomeric proteins, which could contribute to the functional properties of skeletal muscle and the fatigue-resistant phenotype associated with the R577X polymorphism.